Anti-inflammatory and antioxidant activity of high concentrations of hydrogen in the lung diseases: a systematic review and meta-analysis - Xiao, Kang; Liu, Jianwei; Sun, Yuxin; Chen, Shangya; Ma, Jiazi; Cao, Mao; Yang, Yong; Pan, Zhifeng; Li, Peng; Du, Zhongjun (Frontiers in Immunology, 2024)
As a small molecule, hydrogen is colorless, odorless and lightest. Many studies conducted that hydrogen can protect almost every organ, including the brain, heart muscle, liver, small intestine, and lungs. To verify whether high concentrations of hydrogen (HCH) has anti-inflammatory and antioxidant activities on respiratory system, we product a systematic review and meta-analysis. We investigated MEDLINE-PubMed, Cochrane Library, ScienceDirect, Wiley and SpringerLink database and selected in vivo studies related to the anti-inflammatory or antioxidant effects of HCH in the lung diseases which were published until September 2023. We firstly identified 437 studies and only 12 met the inclusion criteria. They all conducted in rodents. The results showed that HCH had a positive effect on the reduction of tumor necrosis factor alpha (TNF-α), interleukin (IL)-1β, IL-4, IL-8, malondialdehyde (MDA), superoxide dismutase (SOD) and reactive oxygen species (ROS); but there is no effect on IL-6, we speculated that may contribut to the test results for different body fluids and at different points in time. This meta analysis discovered the protective effects on inflammation and oxidative stress, but whether there exists more effects on reduction of inflammatory and oxidant mediators needs to be further elucidated.